A Statistical study on Atlanta Industries, Inc. - Butac, Aleczar Monis; Lagunay, Novis; Sanchez, Richard (Diliman, Quezon City College of Engineering, 2001)
Atlanta Industries, Inc. is a manufacturing company that employs the extrusion process in the production of pipes and piping systems. Currently, rejection rates have caused profit losses due to the variability of the wall thickness of Blue In-House Potable Water Pipes. Problem analysis showed one factor that could have caused the variability of the thickness, which was the pulling rate. Goodness of Fit Test, Non-Parametric : One-Sample Sign Test, Linear Regression Modeling, Analysis of Variance and Duncan's Multiple Range Test were the test statistics used in analyzing and interpreting the gathered data. Results revealed that the pulling rate from the extrusion machine had a 78 percent linear relationship with the wall thickness of extruded pipes. Also, the low speed setting of 1.10 cm/s to 1.50 cm/s was the most different from the other settings. It was concluded that the low speed setting caused the variability of the wall thickness and thus the high rejection rates in the production. The group recommended that the company must not use a low speed setting in producing pipes with 3.6-4.2 mm wall thickness. Also, the company must check the puller if it might have mechanical defects that need corrections.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 28 : Statistical Analysis for Industrial Engineering
Keywords: Statistics